Formulation and in vivo evaluation of fast disintegrating tablets containing avocado seed extract as an antidiabetic agent in male rats - Ali Nofriyaldi; Sri Rohmawati; Alma Asyyaidah; Ratna; Silmi Sabila; Hana Lutpia (Pharmaciana, 2026)
Avocado seeds, often considered agricultural waste, contain bioactive compounds, such as flavonoids and alkaloids, with promising antidiabetic properties. This study aimed to develop fast disintegrating tablet (FDT) formulations utilizing avocado seed extract with varying concentrations of the superdisintegrant croscarmellose sodium (2%, 4%, 6%, and 8%). The tablets were evaluated for their physical characteristics, including hardness, friability, disintegration time, and uniformity of weight, to ensure compliance with pharmacopeial standards. All formulations demonstrated acceptable physical properties, indicating that the incorporation of avocado seed extract did not compromise tablet quality. In vivo testing was conducted in diabetic mice to assess the antidiabetic activity of each formulation. The results revealed that all FDTs were effective in reducing blood glucose levels, with the formulation containing 8% croscarmellose sodium showing the most significant hypoglycemic effect. This enhanced activity is attributed to the rapid disintegration and improved bioavailability of the active compounds, which allows a faster onset of action. The findings suggest that avocado seed extract can be successfully formulated into fast-disintegrating tablets, providing a novel and efficient delivery system for antidiabetic therapy. Moreover, the utilization of avocado seed waste highlights the potential of natural resources in pharmaceutical innovation, offering both therapeutic benefits and sustainable value.